Allyl Phosphonium Salt-Modified Clay for Photocured Coatings: Influence on the Properties of Polyester Acrylate-Based Coatings - ÇAKMAKÇI, EMRAH; KAHRAMAN, MEMET VEZİR (WILEY, 2015)
In this study, bentonite clay was modified with a phosphonium salt and this modified clay was used to prepare polyester acrylate based coatings to improve their flame retardancy and mechanical properties. Photocured composites were prepared with 1, 2, and 3 wt% phosphonium salt modified clay and for comparison 1 wt% nonmodified clay containing composites were also prepared. Modified clay displayed good dispersion properties due to its increased basal spacing. Composites were characterized by FT-IR and XRD measurements. According to XRD results, it was found that the modified clay was exfoliated in the composites. Furthermore, we investigated the effect of allyl phosphonium salt modified clay on the thermal, mechanical, and flame retardant properties of polyester acrylate based composites coatings. When compared with neat clay containing coatings, modified clay containing photocured coatings exhibited increased modulus and enhanced thermal properties due to increased crosslinking density. Moreover, the presence of the phosphonium salt enhanced the flame retardancy of the polyester based coatings. POLYM. COMPOS., 36:946-954, 2015. (c) 2014 Society of Plastics Engineers
Keywords: MECHANICAL-PROPERTIES; NANOCOMPOSITES; BEHAVIOR